A study on patients with coronary artery disease with special reference to bone mineral density - Ete, Tony; Khan, Shakeel Ahamad; Wankhar, Baphira; Pala, Star; Malviya, Amit; Mobing, Habung; Naku, Narang; Bamon, Amethyst; Kumar, Utpal; Kumar, Arun; Fanai, Vanlalmalsawmdawngliana; Pohlong, Stephenson; et al. (International Journal of Research in Medical Sciences, 2020)
Background: Osteoporosis and Coronary artery disease are known to share common risk factors, like inflammation, but a direct relationship between the two has not been established. Some of the previous studies showed low BMD (osteoporosis and/orosteopenia) as an independent predictive factor for coronary artery disease in ambulatory patients. However, some reports have failed to demonstrate a direct relationship between low bone mineral density (BMD) and CAD or cardiovascular risk factors. This study was carried out to estimate bone mineral density (BMD) in patients with coronary artery disease (CAD) and also to evaluate the association between bone mineral density and coronary artery disease. Methods: Hospital based prospective observational study, involving 96 consecutive patients who were referred for coronary angiography for the evaluation of established or suspected CAD and also patients who had acute coronary syndrome (ACS) are enrolled in this study. BMD was determined for the lumbar spine (L2-L4) and femoral neck using DXA scan. Results: The total number of subjects was 96. Out of 96, 24 (25%) patients were females and remaining 72 (75%) were males. Coronary angiography was carried out in all patients. 42 patients from the total had coronary angiography proven single vessel disease (SVD), 33 patients had double vessel disease (DVD) and 21 patients had triple vessel disease (TVD). DXA scan was carried out in all patients. T- score of neck of femur region and lumbar spine was calculated. Neither the presence of significant coronary stenoses ≥50% in two or more coronary vessels nor the prevalence of severe coronary stenoses ≥70% differed significantly between patients with normal bone density, osteopenia, or osteoporosis (p<0.05, respectively). Conclusions: The result of this study suggests that in patients undergoing coronary angiography for the evaluation of CAD, the prevalence of low BMD is high; however, there is no statistically significant relationship between osteoporosis, osteopenia and coronary artery disease state.